Formation of singularities of solutions to the compressible Euler equations for a Chaplygin gas. (July 2022) - Lai, Geng; Zhu, Mi
Abstract: This paper studies the formation of singularities in classical solutions to the compressible Euler equations for a Chaplygin gas. We give several sufficient conditions on the initial data to obtain that the density itself of the classical solutions to the Cauchy problem for both 1D Chaplygin gas equations and 2D axisymmetric Chaplygin gas equations blows up in finite time.